The director as collaborator - Knopf, Robert, 1961- (Routledge, 2016)
The Director as Collaborator teaches essential directing skills while emphasizing how directors and theatre productions benefit from collaboration. Good collaboration occurs when the director shares responsibility for the artistic creation with the entire production, including actors, designers, stage managers and technical staff. Leadership does not preclude collaboration; in theatre, these concepts can and should be complementary. Students will develop their abilities by directing short scenes and plays and by participating in group exercises.